The Neotropical sharpshooter genus Ruppeliana Young (Insecta: Hemiptera: Cicadellidae): four new species, key to males, and new synonyms - Cavichioli, Rodney R.; Carvalho, Rachel A.; Mejdalani, Gabriel (Zootaxa, 2017)
Four new Brazilian species of Ruppeliana are described and illustrated: R. barbarensis sp. nov., R. grossii sp. nov., R. longiphallus sp. nov., and R. serrana sp. nov., the first from Minas Gerais State and the other three from Rio de Janeiro State. The new taxa can be easily distinguished from other Ruppeliana species by their color pattern and male genitalia morphology. Ruppeliana coronulifera (Stål, 1862) and R. taschenbergi (Berg, 1899) are synonymized with R. signiceps (Stål, 1862). Additionally, a diagnosis of the genus and a key to species are provided.